Effects of smectite dehydration and illitisation on overpressures in sedimentary basins: A coupled chemical and thermo-hydro-mechanical modelling approach. (January 2020) - Tremosa, Joachim; Gailhanou, Helene; Chiaberge, Christophe; Castilla, Raymi; Gaucher, Eric C.; Lassin, Arnault; Gout, Claude; Fialips, Claire; Claret, Francis
Abstract: Diagenetic smectite dehydration and smectite-to-illite transition in clay-rich sediments can contribute to the generation of overpressure in sedimentary basins, because of the release of water associated with these mineralogical reactions. However, the challenge of deciphering the contribution of smectite dehydration and illitisation to fluid pressure amongst other mechanisms generating overpressure requires the different mechanisms at play to be jointly considered. Here, we developed a coupled chemical and thermo-hydro-mechanical code, named SURP, to calculate the overpressure generation in a sedimentary pile because of sediment compaction during its burial, temperature increase, water flow and because of the release of water by clay dehydration and illitisation. For this purpose, a revised thermodynamic model describing smectite dehydration by a solid solution approach was considered, together with the different thermo-hydro-mechanical processes occurring in sedimentary basins. The SURP code was applied to the case study of an overpressured passive margin in the Niger Delta, composed of thick shale layers in a sedimentary pile. In this geological scenario, smectite dehydration was simulated and could explain 10–30% (20–50 bar) of the present day overpressure in the main reservoirs, in addition to compaction disequilibrium. Highlights: Coupled model to decipher the influence of smectite dehydration on overpressures. SURP code for chemical and thermo-hydro-mechanical coupling during sediment burial. Use of a thermodynamic model to describe smectite dehydration by a solid solution approach. In the Niger Delta, 10–30% of the overpressure by smectite dehydration, in addition to compaction disequilibrium.